The Effect of Work-Life Balance, Employee Engagement, and Organizational Commitment on Employee Performance with Job Satisfaction as an Intervening Variable at PT PLN UP3 West Surabaya - Adi Heriyanto; Jamal Abdul Nasir; Kohar Adi Setya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The post-pandemic work environment in high-demand sectors like public utilities has intensified the focus on employee psychological well-being as a key performance driver. This study investigates the complex interplay between Work-Life Balance (WLB), Employee Engagement, and Organizational Commitment on Employee Performance, with Job Satisfaction as an intervening variable, at PT PLN UP3 West Surabaya. Using a quantitative approach, data were collected through a census of all 85 permanent employees and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results confirm that WLB, Employee Engagement, and Organizational Commitment have a significant positive direct effect on both Job Satisfaction and Employee Performance. Furthermore, Job Satisfaction significantly mediates these relationships partially. The study concludes that cultivating these psychological factors is crucial for enhancing performance, offering a validated holistic model grounded in Positive Psychology Theory (PERMA) that provides actionable insights for human resource management in the utility sector